Analytical bond model for GFRP bars to steel fiber reinforced self-compacting concrete - Mazaheripour, H. (2013)
The objective of this study is to present a computational algorithm to analytically evaluate the bond behavior between GFRP bar and steel fiber reinforced self-compacting concrete (SFRSCC). The type of information to be derived is appropriate to study the flexural behavior of SFRSCC beams reinforced with GFRP bars in terms of serviceability limit states requirements; in fact the bond between bars and surrounding concrete influences significantly the crack width and crack spacing. The proposed bond model was established by calibrating the parameters of a multilinear bond-slip constitutive law using the experimental results of pullout bending tests carried out by the authors, taking into account the experimental pullout force versus slip at loaded and free ends. According to the comparison between theoretical and experimental pullout force-slip, an acceptable accuracy of the model was observed. Additionally, by considering the proposed bond-slip relationship, a parametric study was carried out to evaluate the influence of the involved bond-slip law’s parameters on the maximum force transferred to the surrounding concrete. Finally, the development length of two GFRP bars utilized in the experiments (deformed and smooth bars) was determined by means of the proposed model, and it was compared with the values recommended by codes.